Reducing poverty and protecting the environment: the overlooked potential of less-favored lands - Hazell, Peter B. R.; Garrett, James L. (International Food Policy Research Institute, 1996)
Faced with limited resources and the need to feed 90 million more people every year, governments and donors want to know whether they should invest in regions with inherent potential to be highly productive, or in less-favored areas where large numbers of poor farmers live and increasingly overexploit natural resources just to survive. Governments and donors should look more closely at the benefits of investing in the agriculture of less-favored areas. Even without including social and environmental benefits, the line can already be redrawn on what is economically justified. This line may well shift even further in favor of less-favored lands as agricultural research opens up new development possibilities. These investments become even more compelling when the social benefits from reducing poverty, food insecurity, and environmental degradation are considered.